The Development of HOTS-Based Encyclopedia SAKU Book to Enhance Science Literacy Culture in Thematic Learning - Anik Twiningsih; Ruth Karsini (Journal of Learning and Technology, 2025)
The culture of scientific literacy is being urgency in the 21st-century education challenges. 21st-century learning is inseparable from the textbooks used by students. This type of learning tool affects the interest of students in learning participation. The development of the HOTS-based encyclopedia SAKU book in this study is one of the researcher' efforts to enhance the culture of scientific literacy following the demands of 21st-century education. SAKU is an acronym for "Siswa Aktif Kreatif Unggul" or Superior Creative Active Learners. The stages in its implementation are cyclic, they are (1) Thematic lesson plans; (2) encyclopedia SAKU book with 15 minutes reading culture; (3) early learning activities; (4) core activities/scientific literacy; and (5) HOTS-based final activities. Data collection techniques using observation, interviews, and tests. Based on the results of the calculation of the effect size data, it shows that the HOTS-based encyclopedia SAKU book in the class I thematic learning had a large positive impact on enhancement the science literacy culture of students with the effect size criteria classified as large. The innovative work of developing the HOTS-based encyclopedia SAKU book had been disseminated through a teacher forum that the principal had identified as the result of innovative work by classroom teachers in supporting thematic learning, especially grade I thematic learning and is oriented towards building a reading culture, especially a culture of scientific literacy.